Manajemen Sarana Dan Prasarana Dalam Meningkatkan Efektifitas Kinerja Pegawai Di Kementerian Agama Kabupaten Lamongan - Imamah, Zahwa Najwatul; Kholis, Nur; Sulanam, Sulanam (Universitas Pakuan, 2025)
MANAGEMENT OF FACILITIES AND INFRASTRUCTURE IN IMPROVING THE EFFECTIVENESS OF EMPLOYEE PERFORMANCE AT THE MINISTRY OF RELIGION OF LAMONGAN REGENCY Infrastructure management is a crucial aspect in supporting the implementation of government agencies' duties and functions. Adequate infrastructure plays a significant role in creating an effective, efficient, and productive work environment. This article aims to describe the implementation of infrastructure management at the Ministry of Religious Affairs Office in Lamongan Regency and to analyze the extent to which it impacts employee performance effectiveness. This study employed a qualitative descriptive method, with data collection techniques including in-depth interviews, direct field observations, and documentation studies of office administration data. The results indicate that infrastructure management involves several stages: needs planning, procurement of goods and facilities, routine maintenance, and the elimination or replacement of unusable assets. This structured and sustainable management approach has been shown to positively impact employee performance effectiveness. Complete, well-organized, and well-conditioned work facilities can improve work morale, environmental comfort, and efficiency in task execution. Furthermore, leadership support in monitoring and budget allocation is also a crucial factor in maintaining the sustainability of infrastructure management. Thus, optimal management of facilities and infrastructure not only improves the quality of public services, but also becomes one of the key strategies in realizing professional and highly competitive governance.